Metacognition in animals: Trends and challenges - Crystal, Jonathon D. (Comp Cogn Behav Rev, 2009)
There is widespread agreement that metacognition is not demonstrated if alternative explanations account for putative meta-cognition data. However, there is less agreement on which studies are protected from alternative explanations. We have argued that existing experiments on uncertainty monitoring can be explained by low-level explanations without assuming metacognition (Crystal & Foote, 2009). The field would benefit from the development of accepted standards for what is required to produce a convincing example of metacognition in animals.